Mean Data for phenotype based clustering, and diversity of common bean genotypes in seed iron concentration and cooking time - Amongi, Winnyfred; Stanley, Tamusange Nkalubo; Mildred, Ochwo-Ssemakula; Arfang, Badji; Isaac, Onziga Dramadri; Thomas, Lapaka Odongo; Ephraim, Nuwamanya; Phineas, Tukamuhabwe; Paulo, Izquierdo; Karen, Cichy; James, Kelly; Mukankusi, Clare (2023)
Mean Data for Iron (FESEED), Zinc (ZNSEED), Cooking Time (COOKT), Yield, Days to 50 flowering (DF), Days to 50% physiological maturity (DPM), pedigree, gene pool, genotype-based clusters, market class and release (2023-04-15)